Pelatihan Bagi Kader tentang Penyuluhan Pada Kegiatan Posyandu - Tati Nuryati Tati; Henny Hanna (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Posyandu is a form of UKBM that is managed and organized from, by, for, and with the community in the implementation of health development, in order to empower the community and provide convenience to the community in obtaining basic health services (1). Based on the results of a previous survey in Panampangan Village, Banjarharjo District, Brebes Regency, in 2021 there were 655 children under five with cases of malnutrition (2.13%), malnutrition (8.5%), and stunting (11.1%) lower compared to 2019 which was 16.6%. One of the efforts to suppress stunting cases through counseling at the Posyandu is still being carried out by health workers, not yet carried out by cadres, even if there are those who provide counseling it is still perfunctory. Based on this, community service activities train counseling for Posyandu cadres, with the aim of increasing counseling on Posyandu activities using various methods and media according to the goals to be achieved. The community service method goes through the stages: Coordination with village heads, officials, village midwives, and other related parties, identifying Posyandu problems and the role of cadres in counseling at Posyandu, counseling training processes, evaluating and recording reporting. The results of community service through a review of all material both theory and practice by asking questions about the material that has been submitted, where participants who can answer get prizes from the committee, and it turns out that almost all participants can answer all quiz questions with prizes.